Marketing Strategy Using SWOT Analysis and the Marketing Trifecta at PO Damar Laksana - Gustiana, Jedi; Jaya, Rama Chandra (Training & Research Institute - Jeramba Ilmu Sukses, 2025)
To address the challenges of competition in the digital era, this study formulates a comprehensive marketing strategy for PO Damar Laksana, a tourism transportation MSME. The background of the problem lies in the limited adoption of technology, such as minimal digital promotion and the absence of an online booking system, which hinders competitiveness. This research uses a descriptive qualitative method with data collected through interviews, observations, and literature studies. SWOT analysis identifies core strengths in service quality and business legality but also reveals weaknesses in physical infrastructure and digitalization. Key opportunities arise from domestic tourism trends, while threats stem from intense competition. The Marketing Trifecta framework (owned, earned, and paid media) has proven effective in increasing brand visibility and lead acquisition. It is concluded that integWeight SWOT analysis with the Marketing Trifecta can produce an adaptive marketing strategy model to support sustainable business growth.